Primary lymphoma of the liver: clinical and pathological features of 10 patients. Issue 12 (December 1990) - Anthony, P P; Sarsfield, P; Clarke, T
Abstract : Nine out of 10 patients with primary lymphoma of the liver presented in a manner that did not suggest a tumour. The initial diagnoses were chronic active hepatitis in three cases and "granulomatous cholangitis", inflammatory pseudotumour, and anaplastic carcinoma in one case each. Moreover, extensive haemorrhagic necrosis in three cases initially suggested the Budd-Chiari syndrome. All the tumours were diffuse non-Hodgkin's lymphomas like the 50 cases reported previously, but they differed from most of these in that nine were of T cell phenotype. Five were pleomorphic small T cell, two T zone, and two T lymphoblastic lymphomas: only one was centrocytic and of B cell lineage. This report extends the range of clinical manifestations (diffuse hepatomegaly without a tumour), histological appearances (resemblance to chronic inflammatory or vascular liver diseases) and phenotype (of T cell lineage) of primary lymphoma of the liver: these features seemed to be related in this series. Recognition is important as prognosis remains favourable in appropriately treated cases. Although the appearances of the liver biopsy specimens may be difficult to interpret, the destructiveness of the infiltrate is an important clue to the diagnosis.